ANALISIS DAMPAK PEMBETONAN JALAN TERHADAP PERTUMBUHAN USAHA EKONOMI MASYARAKAT KECAMATAN SIBERUT SELATAN KABUPATEN KEPULAUAN MENTAWAI - , YAMFRIDA YULIANE ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Economic growth is often associated with the openness of a region of the interaction with the outside world. Sucth interactions require investment to support the role of accesbility and mobility both internally and with the region surrounding areas. One of the investment needed are roads, whicth is the artery of any fluency aktivities in ecomomic, social and culture. Smootnessh of these aktivities is expented to bring the value of benefits to local economic growth. Purpose of this study is: analyze the impact of the concreting of roads to economic growth in the business community. Data use primary data with the help of the tool using the SPSS 15.0. Target sample is community business owners to use purposive sampling. Data collection was done through queestionnaires with descriftive methods and different test average revenue. The results of this study indicate that analysis of the impact of road concreting on the economic growth of the business community Siberut Subdidtrict district South Mentawai Island with significant positive impact on revenues of economic changes in Rural District siberut, Siberut Estuary south District Mentawai Islands. For a food stall variables have a positive influence while non food stall (garage) providing a positive influence on the economic growth oh the business community. Government needs to encourage development in road infrastructure because it provides multiplier effect are very significant to the community. Keyword: Construction Of Roads, Economic Enterprises, Income Communities